Handbook of media for clinical and public health microbiology - Atlas, Ronald M. 1946-; Snyder, James W.
"Preface Almost 1,800 media are described in the Handbook of Media for Clinical and Public Health Microbiology, including newly described media for the cultivation of emerging pathogens. Diseases caused by emerging pathogens that are responsible for increased rates of morbidity and mortality rates, such as Escherichia coli O157:H7, methicillin resistant Staphylococcus aureus (MRSA), vancomycin resistant enterococci (VRE), and carbapenem resistant enterococci (CRE) have raised special concerns and various media included in the Handbook have been designed for the specific cultivation and identification of these pathogens. Many of the new media included in the Handbook of Media for Clinical and Public Health Microbiology permit the cultivation of bacteria, fungi, and viruses that are currently causing major medical problems around the world. These media are very important for the rapid detection of pathogenic microorganisms and the diagnosis of individuals with specific infectious diseases adn for preventing the spread of pathogens via food, water, and environmental sources. Several of the new media described in the Handbook of Media for Clinical and Public Health Microbiology include chromogenic or fluorogenic substrates that permit the rapid detection of specific pathogens. An important function of the Handbook of Media for Clinical and Public Health Microbiology is to provide descriptions of the media that are used to cultivate and identify microorganisms from clinical specimens and those of public health significance. The Handbook provides a compilation of the formulations, methods of preparation, and applications for media used in clinical and public health microbiology laboratories"--Provided by publisher.